2010
DOI: 10.1002/sca.20183
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of surface topography differences in native and exotic invertebrates in the St. Lawrence River

Abstract: Summary:The texture, or topography, interior of shells from native and exotic mollusks are measured and compared to determine if they can be discriminated. Area-scale fractal analysis is used to calculate relative areas as a function of scale, and the relative areas are used to evaluate the measurements. Measurements from a scanning laser profiler and from confocal and interferometric microscopes are compared, as are measurements of an original and a replica. The relative areas indicate clear differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The scales at which there is a high level of confidence, based on the MSR, are those that can be used to discriminate both used and unused surfaces on the obsidian tools. The results of this pilot study are similar to other research using scale‐sensitive fractal analyses (Brown and Savary, '91; Brown and Meacham, '94; Brown et al , '96; Ulcickas et al , 2001; Zang et al , 2002; Ungar et al , 2003; Scott et al , 2005, 2006; Jordan and Brown, 2006; Cantor and Brown, 2009; Brown and Brown, 2010; Stemp et al , 2009, 2010). Their results demonstrate that fractals (Mandelbrot, '77, '82), specifically those documented using scale‐sensitive fractal analyses, are less dependent on the assessed profile or region.…”
Section: Methodssupporting
confidence: 87%
“…The scales at which there is a high level of confidence, based on the MSR, are those that can be used to discriminate both used and unused surfaces on the obsidian tools. The results of this pilot study are similar to other research using scale‐sensitive fractal analyses (Brown and Savary, '91; Brown and Meacham, '94; Brown et al , '96; Ulcickas et al , 2001; Zang et al , 2002; Ungar et al , 2003; Scott et al , 2005, 2006; Jordan and Brown, 2006; Cantor and Brown, 2009; Brown and Brown, 2010; Stemp et al , 2009, 2010). Their results demonstrate that fractals (Mandelbrot, '77, '82), specifically those documented using scale‐sensitive fractal analyses, are less dependent on the assessed profile or region.…”
Section: Methodssupporting
confidence: 87%
“…Foremost is that the measurements of photographic paper on the kind of scanning laser confocal microscope used in this study are dependent on the objective used to make the measurement. Other studies have shown that the measurements made by an interferometric microscope do not always agree well with those made by a confocal microscope and the resultant relative areas can be higher (Powers et al, ) or lower (Brown and Brown ) than those calculated from confocal measurements. It is not clear how to establish the trueness of a measurement of a surface of photographic paper.…”
Section: Discussionmentioning
confidence: 90%
“…The concern is that the presence of these artifacts raises the potential for correlations of surfaces with other phenomena, or for discrimination of surfaces, to be achievable only on specific lenses, as is the case here. It has been shown that measurement utility does not require a high level of trueness, and that useful discrimination can be made with measurements that do not appear to be true (Brown and Brown, ).…”
Section: Discussionmentioning
confidence: 99%
“…Scale-sensitive fractal analysis has been successfully used to document worn surfaces on various types of materials (Mecholsky and Mackin, '88;Brown and Savary, '91;Rees et al, '91;Brown et al, '96;Zang et al, 2002;Ungar et al, 2003;Scott et al, 2005;Jordan and Brown, 2006;Cantor and Brown 2009;Brown and Brown, 2010). There are a number of analysis programs available; however, we have chosen to use the area-scale fractal analysis algorithm RelA for surface characterization.…”
Section: Surface Roughness and Relative Area (Rela)mentioning
confidence: 99%